Idol, or ideal? the Korean pop idol through critical phenomenology - Reyes, Joanna Ellina S.
Abstract In the present global media landscape, with the ubiquity of technology and communities growing past the physical, cultures converge and diverge to recreate the international, but nonetheless, local. Situated in the context of global phenomena comes the ever-present "celebrity" that has developed in societies all over the world to be a valuable multifaceted entity in itself. This has led to the emergence of the "idol", as such in case of Korean Pop music as a genre that has perpetuated through various locales, including the Philippines.